ANTASEDEN OF INTEREST IN BUYING ANDROID IN STUDENTS - Arif , Muhammad (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
The purpose of this study was to determine and analyze the effect of price and brand image on interest in buying Iphone 12 in students of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra. The approach used in this study is an associative approach. The population in this study were 4,175 students from the Faculty of Economics and Business, Muhammadiyah University of North Sumatra, while the sample in this study used the slovin formula as many as 98 people. Data collection techniques in this study used interview techniques, documentation studies, observation, and questionnaires. The data analysis technique in this study uses Multiple Linear Regression Test, Hypothesis Testing (T Test and F Test), and Coefficient of Determination. Data processing in this study used the IBM SPSS Statistic 23 software program.